DIGITAL ANTHROPOLOGY UNDER THE CONCEPTUAL FRAMEWORK AND THEORY OF TECHNOLOGICAL MEDIATION - Mungpattanasunthon, Sukamon (Journal of MCU Social Science Review, 2020)
This article aimed to present evolution and conceptual framework to study Digital Anthropology through the concept of “Technological Mediation Theory”. This idea was to study and summarise the conceptual frame work of the relations between technology roles to human and society in the previous articles. Therefore, the Technological Mediation Theory has been developed from Phenomenology approach. Martin Heidegger is the original philosopher who presented that the human should aware roles of technology more than being only objects. In contemporary era, the concept has been developed to Post phenomenology. Don Ihde, Peter Verbeek, and Robert Rosenberger are the influential thinker to other scholars in this field. Additionally, the outstanding studies are the influence of Digital Technology that shape or reshape human being and transforming to Digitalization. Generally, Digital Anthropology Studies base on research methodology to investigate the technological roles including Digital technology. Everyday life report is the popular technique that the anthropology chooses to explore social and cultural phenomena, then using the result to discuss and argue the data as Technological Mediation Theory by Don Ihde approaches.